The Influence of 360-Degree Feedback and Performance Appraisal Fairness on Employee Motivation - Eva Fachria (International Journal of Economic and Business Research, 2026)
This study investigates the influence of 360 degree feedback and performance appraisal fairness on employee motivation to improve performance through the mediating role of Leader Member Exchange. The research adopts a quantitative explanatory approach using Structural Equation Modelling to examine causal relationships among the proposed constructs. Data were collected from 207 employees working in formal sector organizations that implemented 360 degree feedback systems. The findings reveal that 360 degree feedback significantly enhances Leader Member Exchange, while performance appraisal fairness also contributes positively to the quality of supervisor employee relationships. Leader Member Exchange demonstrates a significant positive effect on motivation to improve performance. The mediation analysis further confirms that Leader Member Exchange serves as a significant mechanism linking both 360 degree feedback and performance appraisal fairness with employee motivation. The results indicate that employees are more motivated to improve performance when appraisal practices are perceived as fair and are supported by strong relational exchanges characterized by trust, respect, and support. The study contributes to performance management literature by highlighting the central role of relational dynamics in transforming appraisal practices into motivational outcomes.